Mutant Muddle: Some Arabidopsis eds5 Mutant Lines Have a Previously Unnoticed Second-Site Mutation in FAH1. Issue 1 (4th November 2019) - Veeragoni, Sravani Ram; Lange, Birgit; Serrano, Mario; Nawrath, Christiane; Bauer, Sibylle; Schäffner, Anton Rudolf; Thordal-Christensen, Hans; Durner, Jörg; Gaupels, Frank
Abstract : Some of the salicylic acid-deficient Arabidopsis eds5 mutants have an unnoticed fah1-2 background mutation, which could cause salicylic acid- and EDS5-independent mutant phenotypes.